Enhanced bio-minerals production using catalysts to accelerate resource recovery in wastewater treatment plants. - Colston, Robert (Cranfield University, 2023)
The biomineralisation mechanisms of five known bio-struvite producing microbes have been established and their ability to recover said biomineral from synthetic solutions and sludge dewatering liquors has been trialled. There is a lack of evidence and knowledge how these microbes perform in open culture conditions and the impact encapsulating media has on their ability to remove and recover orthophosphate as bio-struvite. In this PhD thesis, these microorganisms (Brevibacterium antiquum, Bacillus pumilus, Halobacterium salinarum, Idiomarina loihiensis, Myxococus xanthus) were investigated initially, this was streamlined into investigating encapsulated cultures of B. antiquum and B. pumilus in wastewaters under open culture conditions. The inoculation of all five microbes in source-separated urine in open culture conditions showed growth rates as high as 0.18 1/h and high nucleic acid proportions >80% within 24 hours of incubation. An orthophosphate removal of up to 70% was achieved by B. antiquum inoculations and was increased to 100% when magnesium was increased to a 1:1, P:Mg. Encapsulated cultures of B. pumilus were incubated B4.1 growth media, the removal of orthophosphate and chemical oxygen demand was equal to suspended cell inoculations of B. pumilus. In pure culture and open culture sludge dewatering liquors, encapsulated cultures of B. pumilus and B. antiquum, removed 55% and 70% of the initial orthophosphate over 24 hours respectively. The minimal difference in orthophosphate removal between pure and open culture conditions indicates that encapsulation provided an environmental advantage to the selected microbes to out compete the native species within the open culture sludge dewatering liquors. Suspended cell inoculations into open culture sludge dewatering liquors did not remove any more orthophosphate than non-inoculated controls. In continuous reactors fed by open culture sludge dewatering liquors orthophosphate removal for both encapsulated microbes averaged between 20% and 30%, at phosphorus loading rates of 0.4 kg P/m³ .d and 0.6 kg P/m³ .d. Supplementing a carbon source to the equivalent of 150 mg sCOD/L and increasing the ratio of P:Mg to 1:1.5, achieved an orthophosphate removal of 96% on average by encapsulated B. antiquum. Bio-struvite recovered from all open culture wastewaters was euhedral, prismatic and tabular and was typically coated in a secondary abiotic calcium phosphate. Micropollutant analysis showed the recovered minerals were below international heavy metal limits and were absent from faecal coliforms, pharmaceuticals and other micropollutants for fertilisers. Potential end users and consumers from the public and industry showed a strong willingness to use and eat produce grown from recycling derived fertilisers. There remains to be optimisation of the biomineralisation technique to improve the efficiency of recovery and streamline the operational set up, however the data collected in this PhD strongly supports the development of this technique into industry and will satisfy a growing need for circular economies and closing the nutrient loop.
Keywords: Biomineralisation; bio-struvite; source-separated urine; open culture conditions; phosphate removal; phosphorus recovery; encapsulation; biocatalyst; Brevibacterium antiquum; Bacillus pumilus; sludge dewatering liquors; sustainable fertiliser; recycling derived fertilisers; biomineral recovery; end-users; consumers; circular economy; nutrient loop